1882–1883 Ga. Laws 48– - (:unkn) unknown (General Publisher, 1883)
Prohibited the concealed carrying of any “pistol, dirk, sword in a cane, spear, Bowie-knife, or any other kind of knives manufactured and sold for the purpose of offense and defense.”
--
Keywords: CARRY - CONCEALED